#TITLE_ALTERNATIVE# - (NIM : 22410003) ; (Pembimbing : Dr. Eng. Totok Suprijo), SUHAEMI
In this research, a model was developed to represent the process of coastline change due to the installation of structures parallel to the beach. This model is also used to describe formation process of Tombolo and salient due to the structures, the influence of the structures geometry itself, and also the influence of sediment sources availability. These offshore breakwater structures caused the damping of the wave energy and the deposition of the sediments which was lead to the change of the coastline. Data from field study was adapted to design the simulation. During 2005-2006, there was in average ± 1.49 m shoreline change. A significant change can be observed behind the shadow areas (salients formed up to ± 12 meters). The simulation and field data shows same pattern and there is only relatively small error (0,6 m or 1,1 % - 2,6 %.) that was found. Tombolo and salient were formed if there is big ratio between B / S and small ratio between X/B. It is proven that tombolo will be formed if the ratio of B/S is greater than or equal to 0.97. Moreover, our study has demonstrated that correlation between B / S and X / B reaching 99.19% and there is a strong correlation (96.78%) between the availability of the transport sediment and the formation of Tombolo and salient.